Tumor-Associated Macrophages Correlate With Prognosis in Medulloblastoma - Zhang, Jin; Yuan, Xia; Wang, Yuan; Liu, Jingjing; Li, Zhigang; Li, Shuting; Liu, Yan; Gong, Xiaojun; Sun, Yanling; Wu, Wanshui; Sun, Liming; Du, Shuxu; et al. (Frontiers in Oncology, 2022)
Purpose: Macrophage polarization plays an essential role in the tumor microenvironment of brain tumors. However, the role of tumor-associated macrophages (TAMs) in medulloblastoma still remains controversial. Thus, we investigated the distribution of macrophages in medulloblastoma tissues and analyzed the association of TAM recruitment and medulloblastoma patients’ outcomes. Methods: We obtained a total of 71 paraffin sections from patients with medulloblastoma, and detected the activated phenotype (M1/M2) by monoclonal antibodies for CD68, HLA-DR and CD163 with multiple fluorescence immunohistochemistry method. The number of polarized macrophages was quantified using the InForm software. Outcomes were analyzed according to clinical data and quantified macrophage data. Results: The study revealed that TAMs were significantly higher in sonic hedgehog (SHH) medulloblastoma than in other subgroups, and M1 macrophages in metastatic group were significantly higher than those in non-metastatic group. A Kaplan-Meier survival analysis and multivariate Cox regression model showed the correlation of high percentage of total macrophages (P = 0.038, HR = 0.241) and M1 macrophages (P = 0.034, HR = 0.333) with good 5-year progression-free survival (PFS); however, M2 macrophages had no correlation with survivalof medulloblastoma patients (P> 0.05). Conclusion: High percentage of total macrophages and M1 macrophages were correlated with good outcome of medulloblastoma patients. TAMs might be a target of therapy.